Drug‐induced ototoxicity: Mechanisms, Pharmacogenetics, and protective strategies. Issue 4 (3rd February 2017) - Lanvers‐Kaminsky, C; Zehnhoff‐Dinnesen, AG am; Parfitt, R; Ciarimboli, G
Abstract : Drug ototoxicity limits the quality of life of patients after treatment, having serious consequences, especially for psychosocial development of children. Although the ototoxicity of many drugs resolves after treatment discontinuation, the use of platinum derivatives and aminoglycosides is associated with permanent hearing loss. In this review, we have listed ototoxic drugs and the mechanisms by which they damage the ears. Moreover, possible protective strategies and important methods for early detection of ototoxic effects are discussed.